The Role and Effectiveness of the Literary Text in Achieving the Functionality of Linguistic Acquisitions within the Framework of the Textual Approach - djabiri, sonia; mellaoui, alamin (El Omda in Linguistics and Discourse Analysis, 2023)
The present paper seeks to showcase the effectiveness of the teaching of Selected Literary Texts and to uncover its efficiency in achieving the pedagogical objectives figuring in the curriculum. The Literary Texts within the Text Approach represent the corner stone in all overlapping and comprehensive language branches aiming to build the required Reception and Production Skills. This concretizes the Self-directed Learning and creativity and leads to an active literary course.